Dynamic voltage restorer-based pi controller using recent optimization algorithm in a microgrid for power quality enhancement - Ahmed Atef Mohamed Zidan; Ahmed M. Ibrahim (2025)
The thesis analyzes the influence of Micro grid (MGw) REs wind systems on voltage quality, harmonic analysis and types of faults conditions. The DVR is a practice power device used most regularly in power distribution. DVR is employed for improving the PQ issues related to the REs. The honey badger algorithm (HBA) is utilized to get the PI controller$1 (Bs gain values for the proposed DVR. HBA is presented to review the PI controller$1 (Bs performance and fast dynamic response. MATLAB simulations have been employed to confirm the proposed DVR's effectiveness.s
(3MGdGJ GdCYWGd(B. (3Gd(B(DVR) (3gh LgGR WGbI JOQjHj ojSJNOe HTcd efJXe aj JhRjY GdWGbI(B. (3jJe GSJNOGe (BDVR (3JMdd GdCWQhMI JCKjQ CfXeI GdQjGM PGJ GdTHcI GdUZjQI (B(MGw) REs (3Ydi LhOI GdLgO hGdJMdjd GdJhGabj hCfhGY dJMSjf eTcdGJ (BPQ (3GdeJYdbI HGd(BREs . (3Je GSJNOGe NhGQRejI ZQjQ GdYSd (B(HBA) (3ddMUhd Ydi bje cSH hMOI GdJMce (BPI (3d (BDVR (3GdebJQM(B. (3jJe JbOje (BHBA (3deQGLYI COGA hMOI GdJMce (BPI (3hGdGSJLGHI GdOjfGejcjI GdSQjYI(B. (3Je GSJNOGe YedjGJ eMGcGI (BMATLAB (3dJCcjO aYGdjI (BDVR (3GdebJQMI(B.s
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 56-59.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Electrical engineering; (3gfOSI GdcgQHjIs; Power quality -- dynamic voltage restorer -- optimization -- renewable energy sources; -- honey badger algorithm -- wind energy -- grid faults